Development of Thermoelectric Generator for Energy Saving Device Using Exhaust Waste Heat in Patrol Boat - Yudha Sukma Perdana; Cahya Kusuma (International Journal of Marine Engineering Innovation and Research, 2023)
This study describes the energy wastage of diesel engines on patrol boats. Patrol boats typically have high speeds and large engines that waste a lot of heat. This research focuses on research on diesel engines as main engines and generators. Diesel engine combustion results in only about 30~40% available as mechanical energy. Waste heat energy from combustion that is not used as mechanical energy is released to the environment in the form of exhaust gases. The thermal energy of the exhaust gas from engine combustion inside the patrol boat is wasted and cannot be used. The thermoelectric generator concept converts unusable thermal energy from the exhaust gases into electrical energy that can be used by the patrol vessel. The device setup with series and parallel connections was tested on a patrol boat diesel generator engine. Exhaust heat causes an average engine temperature of 110°C and can produce a voltage of 12.85 volts DC and 5.88 watts of electrical energy when connected in series and a voltage of 1.5 volts when connected in parallel. Produces DC and power with 1.44 watts of energy. By utilizing hitherto neglected engine waste heat, thermoelectric generators are a potential alternative energy harvesting technology with the concept of waste heat energy recovery systems.